Pengenalan Kompetensi Sosial Emosional: Wawasan dan Keterampilan untuk Remaja - Sutanto, Sandra; Oktafiana, Rhema; Shalom, Joia Putri; Togatorop, Clara Shinta Ayu (Fakultas Psikologi Universitas Pancasila, 2024)
School counselors at Dian Harapan Lippo Village are confronted with students who consistently exhibit anxiety in both academic and non-academic domains. Poorly managed emotions not only affect academic performance but also disrupt social relationships with peers, teachers, and parents. Social emotional competence is crucial for adolescents as they navigate daily life stressors. A deficiency in social emotional competence can lead to emotional instability, resulting in increased stress and anxiety among adolescents. To address this, informational and skill-based interventions were provided through a series of mini seminars. The methodology included briefings on social emotional competency skills, reflective learning, and role-playing exercises to facilitate the application of the material. The seminars were targeted at students in grades 9 and 11, who are preparing for graduation exams and selecting their academic majors. Among the participants, 84 students provided feedback, with evaluations ranging from good to very good regarding the seminar's effectiveness.